Chemical composition and medicinal properties of mint (mentha) growth - Jumayeva Dinora Omon qizi (Zien Journals, 2023)
In this article, the importance of the medicinal properties of the mint plant in the national economy and folk medicine is highlighted.
Keywords: Mentha; India; spices